2012
DOI: 10.1093/aob/mcs287
|View full text |Cite
|
Sign up to set email alerts
|

Secreted pitfall-trap fluid of carnivorous Nepenthes plants is unsuitable for microbial growth

Abstract: The secreted liquid of closed and freshly opened Nepenthes pitchers is exclusively plant-derived. It is unsuitable to serve as an environment for microbial growth. Thus, Nepenthes plants can avoid and control, at least to some extent, the microbial colonization of their pitfall traps and, thereby, reduce the need to vie with microbes for the prey-derived nutrients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 31 publications
6
62
1
2
Order By: Relevance
“…Compared to Sarracenia, the pitcher fluid in Nepenthes contained higher activity of digestive enzymes with higher concentrations of antibacterial agents making more extreme conditions for adaptation of the bacteria [9,44]. Recent studies have attempted to assess the bacterial community in cultivated Nepenthes pitchers from 16S rRNA gene sequences by using the clonal library method [26,45]. However, the diversity generated by this method was limited by the depth of sequencing (i.e., number of sequences per sample).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to Sarracenia, the pitcher fluid in Nepenthes contained higher activity of digestive enzymes with higher concentrations of antibacterial agents making more extreme conditions for adaptation of the bacteria [9,44]. Recent studies have attempted to assess the bacterial community in cultivated Nepenthes pitchers from 16S rRNA gene sequences by using the clonal library method [26,45]. However, the diversity generated by this method was limited by the depth of sequencing (i.e., number of sequences per sample).…”
Section: Discussionmentioning
confidence: 99%
“…Although indirect evidence for the former are available for Nepenthes [15,16], these studies are not without criticism, and do not demonstrate unequivocally the benefit derived from microbial colonization of its pitchers. By contrast, a growing number of studies in more recent years have shown that pitcher secretions are anti-microbial, an observation that seems to point in the direction of an antagonistic relationship between plant and fluid microbes [17][18][19].…”
Section: Introductionmentioning
confidence: 95%
“…However, we hypothesized that Nepenthes and Sarracenia could have different microbial biota because of certain specific characteristics. First, the fluid in unopened Nepenthes pitchers may already contain microbes ( [8,62]; but see [6]), the origin of which is still uncertain, although they may come from the phyllosphere. In contrast, it was reported that Sarracenia pitchers are sterile before opening [22,49,50], so prey and/or debris falling into the pitchers may facilitate the initial microbial colonization after pitcher opening.…”
Section: Introductionmentioning
confidence: 99%